A transimpedance amplifier for optical communication network based on active voltage-current feedback. (September 2017) - Seifouri, Mahmood; Amiri, Parviz; Dadras, Iman
Abstract: In this paper, a new topology is proposed for designing and analyzing a transimpedance amplifier (TIA) based on active voltage-current feedback. The proposed topology reduces the input and output impedances by using a common source transistor as a voltage-current feedback. In this topology instead of using a resistor to convert current to voltage, we convert transistor transconductance into transimpedance, and then by applying an electrical current to the drain the required voltage appears at the gate terminal. Simulation of the designed TIA for 1.8 V 0.18 µm CMOS technology shows that the gain of 59 dBΩ with 1 dBΩ gain ripple of the bandwidth of 7.9 GHz can be achieved. While the whole TIA circuit consumes 18 mW from 1.8 V power supply the simulated average input current noise spectral density is about 23 pA / √ Hz within the TIA frequency band. In this topology new tradeoffs are possible which make a further degree of freedom which are not available in previous topologies.